Characterization of the EPS from a thermophilic corrosive consortium. Issue 10 (26th November 2019) - Atalah, J.; Blamey, L.; Gelineo-Albersheim, I.; Blamey, J. M.
Abstract: Biofilm forming microorganisms are known to contribute to the corrosion of metallic materials, as they can attach to surfaces and influence the electrochemical behavior. Extracellular polymeric substances (EPS) produced by these microorganisms play a major role in adhesion and resistance of the biofilm, thus also contributing to corrosion. A better understanding of the composition of EPS could help mitigate the impact of bacterial mediated corrosion. Here, a preliminary characterization of the EPS from a thermophilic consortium isolated from a corroded airplane engine is presented. Analysis revealed five different monosaccharides, with predominance of glucose and manose, but also a significant amount of rhamnose. Glycosyl linkage analysis was also performed. On the lipid fraction, three types of fatty acids were found. The predominant protein found by peptide finger printing was S-Layer protein, related to bacterial adhesion. Morphological characterization of the biofilm forming consortium was carried using confocal and scanning electron microscopy.